The location of transcultural memory in Vikram Seth's memoir Two Lives (2005). (22nd November 2019) - Butt, Nadia
ABSTRACT: This article seeks to investigate the different dimensions of transcultural memory; it particularly scrutinises it with reference to travelling, dialogic and postmemory. The aim of such an approach is to discuss transcultural memory in relation to migrants, expatriates and exiles, highlighting the ways in which their memories tend to cut across national, cultural, ethnic and geographical borders. Having addressed the transcultural turn in the field of memory studies, I closely examine transcultural memory in Vikram Seth's memoir Two Lives in order to address broader issues of diasporic identities and the coming together of Indian and European histories within a memory narrative. Set mostly in Germany and England, Two Lives recounts individual histories—at first parallel, and separated, but later intertwined—of Seth's great-uncle Shanti Seth and his German-Jewish wife Hennerle Caro. These two lives, I argue, serve as a historical document, revealing how family histories turn out to be a unique manifestation of "global memories" such as the Holocaust, the Second World War, or the partition of India. The article, hence, demonstrates that as the narrator chronicles overlapping family histories, he makes the reader imagine transcultural memory as a constant process of change and discovery rather than a permanent condition. Finally, I maintain that Seth's work, with its tale of human dialogue across cultural barriers, provides a new perspective on memory, culture, history and territory as shared, overlapping and intertwined.